Factors Associated with Perceived Abuse in the Health Care System Among Long-Term Opioid Users: A Cross-Sectional Study. (11th May 2016) - Palis, Heather; Marchand, Kirsten; Peng, Defen; Fikowski, Jill; Harrison, Scott; Spittal, Patricia; Schechter, Martin T.; Oviedo-Joekes, Eugenia
ABSTRACT: Background : Opioid-dependence is a chronic relapsing disorder. Histories of physical, sexual, and emotional abuse are prevalent among long-term opioid users. While perceived abuse in health care has been linked to histories of abuse in other populations it has not been investigated among long-term opioid users. Objective : To determine factors associated with perceived abuse in health care among a sample of long-term opioid users. Methods : Gender Matters in the Health of Long-Term Opioid Users (GeMa) was a descriptive cross-sectional study. Participants ( n = 175) answered questions on health, drug use, treatment history, and victimization. A multivariable model of perceived abuse in health care was built using logistic regression. Results : Half of participants ( n = 88) reported perceived abuse in health care in lifetime with no gender differences. Histories of abuse, physical, and psychological health problems, and health care access were more prevalent among those reporting perceived abuse in health care compared to those not reporting such experiences. Multivariable analysis showed that more methadone maintenance treatment attempts in life, prescribed psychiatric medication in life, and having higher childhood emotional abuse scores were independently associated with perceived abuse in health care. Among all childhood neglect and abuse types measured, emotional abuse was the only significant predictor. Conclusions : A high prevalence of lifetime perceived abuse in health care (50%) was reported, along with extremely high childhood abuse and neglect scores. Consideration of these variables by health care and service providers is extremely important to improving patient perceptions of care, and ultimately health and treatment outcomes among opioid-dependent people.